2(х-2)(х+2) = (х-4)(х+4)+(х-3)(х+3)+х помогите уравнение решить :D

0 голосов
16 просмотров

2(х-2)(х+2) = (х-4)(х+4)+(х-3)(х+3)+х
помогите уравнение решить :D


Алгебра (15 баллов) | 16 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

Решите задачу:


2{x}^{2} - 8= {x}^{2} - 16 + {x}^{2} - 9 + x \\ 2 {x }^{2} - 2 {x}^{2} - x = - 25 + 8 \\ - x = - 17 \\ x = 17
(11.2k баллов)
0 голосов

2 • (x - 2) • (x + 2) = (x - 4) • (x + 4) + (x - 3) •(x + 3) + x

2 • (x^2 - 4) = x^2 - 16 + x^2 - 9 + x

2x^2 - 8 = 2x^2 - 25 + x

-8 = -25 + x

- x = -25 + 8

-x = -17

x = 17

@iGeniusOX⚡

(7.5k баллов)